2011
DOI: 10.5539/jsd.v4n5p244
|View full text |Cite
|
Sign up to set email alerts
|

Gas Flaring and its Implication for Environmental Accounting in Nigeria

Abstract: The study examines the theoretical framework for gas flaring and its implication for environmental accounting in the Nigerian Petroleum Industry. Data were sourced from the annual reports of companies involved in gas flaring in the oil and gas industry and the result reveals that the issue plaguing environmental accounting disclosures relate to lack of a standardized requirement for disclosure, political will for legislation, enforcement and the allocation of environmental costs, therefore, the study recommend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…[12] went further to point out that the purpose of industrial development of any region is to promote opportunities of better living and employment to the people but also increase the adverse effect, if not properly controlled or reduced to the barest minimum. The pollution of an environment is one of the most horrible ecological problem the world is subjected today, [13]. [14] also revealed that the environment which comprises of air, land and water was in the past virgin, undisturbed, uncontaminated and basically most hospitable for human and other organisms, but the situation is just the reverse today because of man's interference.…”
Section: Concepts Of Gas Flare On Human Life and Wellbeingmentioning
confidence: 99%
“…[12] went further to point out that the purpose of industrial development of any region is to promote opportunities of better living and employment to the people but also increase the adverse effect, if not properly controlled or reduced to the barest minimum. The pollution of an environment is one of the most horrible ecological problem the world is subjected today, [13]. [14] also revealed that the environment which comprises of air, land and water was in the past virgin, undisturbed, uncontaminated and basically most hospitable for human and other organisms, but the situation is just the reverse today because of man's interference.…”
Section: Concepts Of Gas Flare On Human Life and Wellbeingmentioning
confidence: 99%
“…According to a World Bank sponsored study, gas flaring is one such anthropogenic activity defined as the wasteful emission of greenhouse gases (GHGs) that causes global warming, disequilibrium of the earth, unpredictable weather changes. It is a major natural disaster because it emits a cocktail of benzene and other toxic substances that are harmful to humans, animals, plants and the entire physical environment [13]. Some of the other impacts are listed below;…”
Section: Impacts On the Environmentmentioning
confidence: 99%
“…In addition, a legislation that prohibits gas flaring from 31st of December, 2012 was promulgated by the policy makers and it states that any oil company that pollutes the environment through flaring without the permission of the government will be charge a fine which shall be equivalent to the value of gas (Fawole et al, 2016). However, this policy was not seen as been justifiable because there is no provision of markets where the associated gas can be sold and also lack of infrastructural facilities to capture the associated natural gas (John, 2012).…”
Section: Gas Flaring Policy Impacts Review In Nigeriamentioning
confidence: 99%
“…A number of studies have researched the effect of gas flaring on Niger delta environment. Researches argue that gas flaring increases occurrence of acid rain in the Niger delta area (Adewale & Mustapha, 2015;John, 2012). Another study found that there is concentration of heavy metals in the surface and ground waters (Nwankwo & Ogagarue, 2011) and people of Niger delta are prone to ecological and bacteria disease as a result of gas flaring (Adekola, Fischbacher-smith, & Fischbacher-smith, 2017;Maduka & Tobin-west, 2017).…”
Section: Environmental and Health Effect Of Gas Flaring In Nigeriamentioning
confidence: 99%